Difficulties of Early Childhood Education Teachers in Implementing the Pancasila Student Profile Strengthening Project (P5) At M. Hilir Ismail Kindergarten, Bima City - Muhajira; Agus Salam; Sri Jamilah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the difficulties of teachers in implementing P5 in TK M. Hilir Ismail, Bima City. The P5 program is implemented in stages and requires a long time including planning, implementation and evaluation. This study uses a qualitative descriptive approach. The object of this study is teachers at TK M. Hilir Ismail. Teachers have difficulty in designing activities that are in accordance with the established theme. And teachers have difficulty in directing children during the implementation process of the Pancasila student profile strengthening project (P5). This is caused by the unbalanced teacher and student ratio in TK M. Hilir Ismail, Bima City, which is an obstacle for teachers and the activities carried out are not in accordance with children's interests in implementing the project effectively. Limited facilities and classrooms, lack of textbooks. Problems in the planning aspect, namely teachers at TK M. Hilir Ismail, Bima City have difficulty in determining the forms of activities that are in accordance with the existing theme. Evaluation of the problematic of the Pancasila Student Profile Strengthening Project in the difficulties of PAUD teachers in implementing the Pancasila student profile strengthening project (P5). Thus, teachers need to receive continuous training and provision to overcome this obstacle and can develop assessment instruments that are in accordance with the principles of the Independent Curriculum.